ANALISIS STRATEGI KOMUNIKASI POLITIK I BAGUS ALIT SUCIPTA DALAM PEMILU LEGISLATIF PROVINSI BALI TAHUN 2019 (Jurnal Nawala Politika, 2023)
This study aims to determine the political marketing strategy in the legislative election campaign by one of the candidates, namely I Bagus Alit Sucipta or Gus Bota. In the implementation process, the election campaign, a political marketing strategy is basically needed to build the character and characteristics of the candidates. This study uses the literature review method which is obtained from the analysis of secondary data. There are some findings as follows: First, the 4P marketing strategy (product, promotion, price, and place) that is able to see the process of establishing the services offered by candidates to the public. The second one is the five stages development method by Larson is able to show the feedback from the public towards the products offered by Gus Bota during his campaign process in the legislative elections 2019.